Sustainable traditional markets development in Bogor District - Umar Mansyur (Indonesian Journal of Applied Environmental Studies, 2021)
Bogor District consists 40 sub-districts and 483 villages, with development policy in the development of Metropolitan Jabodetabekpunjur, which makes the potential to grow rapidly. The increase of GRDP value is indirectly affected by the condition of economic activity, including the existence of economic facilities and infrastructures and its sustainability. The objectives of this research are to identify market development location (environmental aspect), to identify market development feasibility (economic aspect), and to draw up the concept of distributed market development (social aspect). This research uses the methodology of agency and field surveys, observations and interviews using descriptive analysis technique, scoring system, descriptive statistics and strategic decision making. The results obtained from this research: there are 26 sub-district traditional markets and 47 village traditional markets by lacks of 450 markets, under the category of 12 most feasible markets, 16 feasible markets, and 12 unfeasible markets; the first optimization model is achieved by Kemang sub-district while the second position is achieved by Dramaga sub-district and the third position is achieved by Ciawi sub-district; and the development in 2018-2038 by the highest population in Gunungputri and the lowest population in Cariu, under total needs of 280 markets and still lacks of 202 markets.